Microparticle-mediated gene delivery for the enhanced expression of a 19-KDa fragment of merozoite surface protein 1 of Plasmodium falciparum - Liu, S.; Danquah, Michael; Forde, G.; Ma, C.; Wang, L.; Coppel, R. (2010)
The 19 kDa carboxyl-terminal fragment of merozoite surface protein 1 (MSP119) is a major component of the invasion-inhibitory response in individual immunity to malaria. A novel ultrasonic atomization approach for the formulation of biodegradable poly(lactic-co-glycolic acid) (PLGA) microparticles of malaria DNA vaccines encoding MSP119 is presented here. After condensing the plasmid DNA (pDNA) molecules with a cationic polymer polyethylenimine (PEI), a 40 kHz ultrasonic atomization frequency was used to formulate PLGA microparticles at a flow rate of 18 mL h1. High levels of gene expression and moderate cytotoxicity in COS-7 cells were achieved with the condensed pDNA at a nitrogen to phosphate (N/P) ratio of 20, thus demonstrating enhanced cellular uptake and expression of the transgene. The ability of the microparticles to convey pDNA was examined by characterizing the formulated microparticles. The microparticles displayed Z-average hydrodynamic diameters of 1.50-2.10 lm and zeta potentials of 17.8-23.2 mV. The encapsulation efficiencies were between 78 and 83%, and 76 and 85% of the embedded malaria pDNA molecules were released under physiological conditions in vitro. These results indicate that PLGA-mediated microparticles can be employed as potential gene delivery systems to antigen-presenting cells in the prevention of malaria. © 2009 American Institute of Chemical Engineers.